Nutritional and Sensory Evaluation of Yogurt Drinks Based on Pure Milk and Low-Lactose Milk with Probiotic Fermentation: Evaluasi Nutrisi dan Sensoris Minuman Yogurt Berbasis Susu Murni dan Susu Rendah Laktosa dengan Fermentasi Probiotik - Lebdoyono, Rendra; Azzahrya, Athaya Bella; Prayitno, Sutrisno Adi (jurnal makanan tropis dan teknologi agroindustri, 2025)
Yogurt is a fermented product that is popular and easily accepted by the public because of its benefits and good nutrition. However, the presence of lactose intolerance disorder caused by milk is an obstacle to getting the benefits of yogurt, so it is necessary to develop by using low-lactose milk in yogurt drink products . This research is an experimental study that aims to compare the nutritional content and sensory value of yogurt drink based on whole milk and low-lactose milk with the addition of L. Plantarum Dad 13. pH test, proximate analysis and sensory analysis of yogurt drink were carried out. The results showed that fresh milk yogurt drink samples had a lower final pH compared to samples using low lactose milk (p>0.05). Meanwhile, the low lactose yogurt had a lower sugar content compared to whole milk-based yogurt (p>0.05). Although the content analysis showed insignificant results, yogurt drink with the addition of L. plantarum Dad-13 showed good nutritional content compared to whole milk yogurt. Sensory test showed that probiotic yogurt drink tended to be preferred due to its flavor and higher acceptance level compared to whole milk yogurt.